Chapter 21 Archaea - Dombrowski, Nina (Taylor & Francis, 2021)
Practical Handbook of Microbiology, 4th edition provides basic, clear and concise knowledge and practical information about working with microorganisms. Useful to anyone interested in microbes, the book is intended to especially benefit four groups: trained microbiologists working within one specific area of microbiology; people with training in other disciplines, and use microorganisms as a tool or "chemical reagent"; business people evaluating investments in microbiology focused companies; and an emerging group, people in occupations and trades that might have limited training in microbiology, but who require specific practical information.